2020
DOI: 10.28955/alinterizbd.737995
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Turmeric Powder (Curcuma longa) on Fatty Acid Composition and Shelf Life of Broiler Chicken Meat

Abstract: The objective of this study was to determine the appropriate concentration of dietary supplementation of turmeric powder, and its effect on thiobarbituric acid reactive substance (TBARS) and fatty acid composition in thigh and breast meat of broiler chickens. Three hundred fifty (175 male and 175 female), one day old Ross-308 broiler chicks were used in this study. A corn-soybean meal based diet containing different levels of turmeric powder (0, 2, 4, 6, 8, 10 g/kg) and a single dose of chlortetracycline (10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Other studies did not find any significant effect of turmeric supplementation at the rate of 1.0 g/kg (Rahmatnejad et al, 2009) or 2.0 g/kg (El-Hakim et al, 2009) on carcass production. Also, Ürüşan and Bölükbaşı (2017) reported that adding turmeric did not affect the carcass yield. Turmeric also improves liver and bile functions through increased bile secretions, protects the stomach from ulcers and reduces liver toxins.…”
Section: Carcass Criteria Of Quails As Affected By Curcumin and Groun...mentioning
confidence: 99%
“…Other studies did not find any significant effect of turmeric supplementation at the rate of 1.0 g/kg (Rahmatnejad et al, 2009) or 2.0 g/kg (El-Hakim et al, 2009) on carcass production. Also, Ürüşan and Bölükbaşı (2017) reported that adding turmeric did not affect the carcass yield. Turmeric also improves liver and bile functions through increased bile secretions, protects the stomach from ulcers and reduces liver toxins.…”
Section: Carcass Criteria Of Quails As Affected By Curcumin and Groun...mentioning
confidence: 99%